2002
DOI: 10.1002/art.10143
|View full text |Cite
|
Sign up to set email alerts
|

Expression of osteopontin at sites of bone erosion in a murine experimental arthritis model of collagen‐induced arthritis: Possible involvement of osteopontin in bone destruction in arthritis

Abstract: Objective. To investigate the involvement of osteopontin (OPN) in bone destruction in a murine experimental arthritis model of collagen-induced arthritis (CIA).Methods. The expression of OPN was examined at both the messenger RNA (mRNA) and protein levels in various arthritic lesions in mice with CIA by in situ hybridization and immunohistochemistry, respectively. In addition, the expression of ␣v␤3 integrin, a receptor for OPN, the ligation of which is thought to be essential for bone resorption by osteoclast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
46
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 28 publications
(31 reference statements)
1
46
0
Order By: Relevance
“…Considering the known properties of OPN as a regulator of inflammation and bone destruction in RA (26,27,41), we suggest that OPN might be a point of contact between inflammation and the consequent articular damage and atherosclerosis in RA. The observed lower OPN levels of non-case and healthy donors led us to speculate that this inflammatory and plaque destabilizing protein is peculiar in RA pathogenesis.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Considering the known properties of OPN as a regulator of inflammation and bone destruction in RA (26,27,41), we suggest that OPN might be a point of contact between inflammation and the consequent articular damage and atherosclerosis in RA. The observed lower OPN levels of non-case and healthy donors led us to speculate that this inflammatory and plaque destabilizing protein is peculiar in RA pathogenesis.…”
Section: Discussionmentioning
confidence: 91%
“…On the other hand, this cytokine is expressed in chronic inflamma-tory and autoimmune diseases (20)(21)(22)(23)(24)(25) with proinflammatory functions, and it has been suggested as a potential mediator of the promotion of joint destruction in RA (26). Enhanced levels of OPN mRNA and protein were found in synovial tissue from RA patients (27). Moreover, OPN deficiency has been shown to protect joints against destruction in arthritis-induced mice-suppressing articular destruction, chondrocyte apoptosis, and synovial angiogenesis (28), suggesting a direct role in bone readsorption beyond its effects on inflammation (29).…”
Section: Introductionmentioning
confidence: 99%
“…Bone resorption by osteoclasts is regulated by the interaction of αvβ3 integrin on osteoclasts and OPN (39). Indeed, we recently found that OPN and its receptor αvβ3 integrin were coexpressed by activated osteoclasts at the site of bone erosion (10).…”
Section: Discussionmentioning
confidence: 99%
“…Anti-TNF-α antibody and IL-1 receptor antagonist are effective in the prevention of both inflammation and joint erosion in early active RA; however, they are unable to completely stop the progression of joint destruction in patients with RA, indicating that the pathological process of RA is complex and that other factors are critically involved (2)(3)(4)(5). Osteopontin (OPN) has been suggested as potential mediator of the promotion of joint destruction in patients with RA through the αvβ3 and αvβ5 integrins expressed on osteoclasts and chondrocytes (6)(7)(8)(9)(10)(11). OPN is an extracellular matrix protein containing an Arg-Gly-Asp (RGD) sequence and upregulated in activated T cells, macrophages, invading synoviocytes, and articular chondrocytes associated with inflammation and tissue repair (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Other mediators, such as osteopontin (OPN), osteocalcin (OCN) and insulin-like growth factor (IGF)-I also influence bone remodeling. OPN is an extracellular matrix protein that is expressed in both synovial cells and chondrocytes in RA, and it can mediate bone resorption by osteoclasts (27). OCN is the most abundant noncollagenous protein of bone, and it is an indicator of osteoblastic activity (28).…”
mentioning
confidence: 99%